Enhancing cropping intensity and system productivity through early-bulking potato genotypes in potato-based cropping systems - Md. Mostahed Hossain; A. K. M. Mominul Islam; Jerina Tasnim; Md. Abdur Rahman Sarkar; Naresh Chandra Deb Barma; Ahmed Khairul Hasan (PLoS ONE, 2026)
Increasing cropping intensity is a key strategy for enhancing food production in regions facing shrinking arable land and rising population pressure. Early-bulking potato genotypes offer opportunities to redesign potato-based cropping systems by creating temporal space for additional crops. This study evaluated the agronomic performance, system productivity, economic returns, and land use efficiency of early-bulking potato genotypes (7 Alu and Sagitta ) within intensified potato-based cropping patterns at the Regional Agricultural Research Station (RARS), Burirhat, Rangpur, Bangladesh during the 2017–2018 cropping year. Thirteen cropping systems, including the conventional potato– boro rice–T. aman rice system, were assessed using a randomized complete block design with three replications. Results showed that incorporation of early-bulking potato genotypes enabled the inclusion of four to five crops per year, substantially increasing system productivity. Potato equivalent yield increased by 43.8–111.5% in the improved patterns compared with the conventional system. The highest land use efficiency (95.61%), whole pattern gross margin (Tk. 538775 ha −1 ), and marginal benefit-cost ratio (8.17) were achieved in the 7 Alu – garden pea – red amaranth – T. aus rice – T. aman rice pattern, while the highest potato equivalent yield (95.37 t ha −1 ) was recorded in the 7 Alu – cardinal – Mungbean – red amaranth – T. aman rice pattern. This study indicates that inclusion of early bulking potato varieties has the potential to serve as effective entry-point crops for intensifying potato-based cropping systems, improving land use efficiency and farm profitability. These findings represent promising outcomes from a single-season trial and highlight the potential of flexible cropping system designs that warrant further multi-year and multi-location validation.